A soft switching non‐isolated bidirectional DC–DC converter with improved voltage conversion ratio and minimum number of switches - Nasrin Asadi Madiseh; Ehsan Adib (IET Renewable Power Generation)
Abstract A soft switching non‐isolated bidirectional DC–DC converter with an improved voltage conversion ratio without any additional auxiliary switch is presented in this paper. In the proposed converter, improved step‐up/step‐down gain conversion is achieved by employing the coupled inductors method. Also, the auxiliary circuit provides soft switching conditions for all the semiconductor elements, regardless of the power flow direction and without any extra voltage stress. The other switch helps provide soft switching conditions for the main switch. Moreover, the switch used for providing soft switching conditions operates as a synchronous rectifier as well. The additional circuit added to attain soft switching is composed of an inductor, coupled with the converter's main inductor, and two auxiliary diodes. The auxiliary diodes benefit from zero‐current‐switching conditions. Fully soft switching conditions for all semiconductor devices, removing the reverse recovery problem, and a low number of components have led to mitigating switching losses and improving efficiency. Detailed operating principles and a theoretical analysis of the proposed converter are presented. Also, the experimental results of a 220 W prototype circuit are provided to confirm the validity of the proposed topology.